Model Motivasi Kerja Dalam Menumbuhkan Semangat Kerja Aparatur Dikantor Kecamatan Panca Rijang - Miska; Rhamadan, Muhammad Rohady; Barisan (UIR PRESS, 2020)
This research is qualitative research that aims to know the motivation of work in fostering the spirit of work apparatus in the Office of Panca Rijang Subdistrict Sidenreng Rappang, which is motivated by the motivation model applied that is a combination of human resources model and human relations model then the implementation of the model that the leader always facilitates employees by providing modern equipment then leaders and employees senentiasa mutual men support in work.The data collection methods used in this study are observation techniques, interviews and documentation. The results of this study show that in facilitating the model of work motivation. Furthermore, leaders should criticize or correct employees in a good way so that social interaction runs well so that a positive and pleasant work atmosphere is achieved.